Methods of Developing Imaginative Thinking through Lyric and Lyrico-Epic Works in Primary School - Gulbakhor Namozova Muzaffarovna (Scientific Trends, 2025)
This article explores the role of lyric and lyrico-epic works in fostering imaginative thinking among primary school pupils. Imaginative thinking is considered one of the essential components of creative and aesthetic development in early education. The paper provides theoretical foundations, methodological approaches, and practical recommendations for teachers on how to use poetic and narrative forms of literature to enhance imagination, emotional intelligence, and interpretative skills. The study also emphasizes the significance of integrating art-based and interactive teaching methods into the learning process.
Keywords: Imaginative thinking, lyric works, lyrico-epic works, primary school, literary education, creativity, teaching methods.